Immersion of Noni Extract Improves Recovery and Reduces Bacteria in Catfish - Yusdiman W. Danial w. danial; Arafik Lamadi; Indra G. Ahmad (Universitas Islam Lamongan, 2026)
Catfish is one of the superior fisheries sectors in the market, but the obstacle often faced by catfish farmers is disease attacks. One of the diseases that often attack catfish is the Aeromonas hydrophila bacteria. An alternative that can be used in the treatment of bacteria in catfish is to utilize antibacterial compounds found in noni fruit (Morinda citrifolia). The purpose of this study was to determine the effective dose of noni fruit solution soaking in the treatment of catfish infected with Aeromonas hydrophila bacteria. This study used a completely randomized experimental design method with 4 treatments and 3 replications carried out for 17 days and was infected intramuscularly with a concentration of 106 CFU/ml of 0.1 ml, with test treatments A (Control), B (30 g/L), C (45 g/L) and D (60 g/L) and soaking using the short bath method for 20 minutes. The results obtained from the study will be subjected to analysis of variance (ANOVA). The results of the study showed that the effective dose was found in treatments B (30 g/L), C (45 g/L) and D (60 g/L) with the observed variables of fish recovery and survival rates being 100%, while the optimal dose for reducing the number of bacteria was found in treatment B (30 g/L) in the kidney section of 0.72 x 107 with a reduction of bacteria of 76.8% while in the liver section it was 0.57 x 107 with a reduction of bacteria of 80.1%.